HIV test uptake among MSM in China: Implications for enhanced HIV test promotion campaigns among key populations - Han, Larry (Glob Public Health, 2016)
Despite global efforts to increase HIV test uptake among men who have sex with men (MSM), social stigma and negative attitudes toward homosexuality hinder the effectiveness of traditional test promotion campaigns. Increasing HIV test uptake requires greater understanding of the conditions that facilitate decisions to get tested. We conducted an online survey hosted by two of the most highly frequented MSM web portals in China. A generalised ordered logistic regression analysis was conducted to determine factors associated with HIV testing behaviour. Compared to men who had never tested for HIV, men who had tested in the past year were more likely to have never engaged in sex with women, have multiple male sex partners in the past 3 months and have disclosed their sexual orientation to others. MSM found testing at local Chinese Centers for Disease Control and Prevention (80.7%), gay men’s community-based organisations (80.2%) and public hospitals (70.9%) to be acceptable, while saunas (50.5%) and gay bars (41.8%) were found to be unacceptable testing venues. Our study shows that MSM in China prefer to test at venues that guarantee confidentiality, quality and quick results. Our study also suggests that self-testing may be a feasible approach to increase test uptake.